Application of Biofertilizers in crop production: A review - Sharma, Barsha (2022)
Nutritious foods are needed for the continuously growing population together with the nutrient for plant growth and production. Inorganic chemical-based fertilizers have been base and are used heavily in today’s soil management procedures, posing serious health and environmental concern. Biofertilizer has been recognized as a reasonable solution for improving soil fertility and crop output in sustainable farming. The use of beneficial microorganisms as biofertilizers has escalated its importance in the agricultural industry due to its potential significance in food safety and sustainable crop production. Biofertilizers can be a valuable component of a comprehensive nutrient management strategy. Overall, nitrogen fixers (N-fixers), potassium and phosphorus solubilizers, growth-promoting rhizobacteria (PGPR), endo and ectomycorrhizal fungi, cyanobacteria, and other beneficial microscopic organisms are incorporated into biofertilizers. Utilizing bio-fertilizers, enhance nutrient and water uptake, plant development, and plant tolerance to abiotic and biotic impacts. These prospective biological fertilizers would play a essential role in soil production and sustainability and also in environmental protection, being eco-friendly and cost-effective inputs for farmers.